Prognostic significance of cytogenetic abnormalities in T‐cell prolymphocytic leukemia. Issue 5 (27th February 2017) - Hu, Zhihong; Medeiros, L. Jeffrey; Fang, Lianghua; Sun, Yi; Tang, Zhenya; Tang, Guilin; Sun, Tsieh; Quesada, Andres E.; Hu, Shimin; Wang, Sa A.; Pei, Lin; Lu, Xinyan
Abstract: T‐cell prolymphocytic leukemia (T‐PLL) is an aggressive mature T‐cell neoplasm. The most common cytogenetic abnormality associated with T‐PLL is inv(14)(q11.2q32) involving TCL1, but other abnormalities also have been reported. In this study, we correlated cytogenetic abnormalities with clinical outcome in 97 T‐PLL patients, including 66 men and 31 women with a median age of 63 years (range, 34‐81). Twenty‐seven patients had a normal karyotype (NK), one had two chromosomal aberrations, and 69 had a complex karyotype (CK). Patients with a CK had poorer overall survival (OS) than patients with a NK ( P = .0016). In the CK group, the most common aberrations involved 14q (n = 45) and 8q (n = 38). Additional deletions of chromosomes 17p, 11q, 6q, 12p, 13q were observed frequently. No individual cytogenetic abnormality impacted OS. Patients with ≥5 aberrations had an OS of 11 months versus 22 months in patients with <5 aberrations ( P = 0.0132). Fluorescence in situ hybridization for TCL1 successfully performed in 27 cases showed rearrangement in 8/10 (80%) NK versus 16/17 (94%) CK cases. OS of patients with TCL1 rearrangement and/or 14q aberrations was not significantly different from patients without TCL1 rearrangement and 14q aberrations ( P = .3467). Patients with refractory disease showed worse OS in both the NK and CK groups ( P = .0014 and P < .0001, respectively), compared with patients who achieved remission but then relapsed. Stem cell transplantation did not appear to improve OS regardless of karyotype complexity. In conclusion, patients with T‐PLL often have a CK which is a poor prognostic factor, particularly in patients with ≥5 cytogenetic aberrations.